Empowering the Local Community through Digital Content Creation for Tourism Village Marketing - Taufiqqurrachman Taufiqqurrachman; Ringgo Eldapi Yozani; Mashur Fadli; Fahmi Muhammad; Riau Nurita (Jurnal Masyarakat Madani Indonesia, 2026)
The community engagement program focused on a tourism marketing training held in Sungai Petai Village, Kampar Regency, which adopted three key approaches—destination image, halal tourism, and sustainable tourism—within a rhetorical structure framework. The main objective was to enhance local capacity in producing compelling marketing content for village tourism by utilizing digital platforms effectively. Initiated by a team of academics from the Faculty of Social and Political Sciences, Universitas Riau, the program applied a problem-based learning method and was evaluated through three levels of assessment: reaction, learning, and behavior, involving a total of 30 participants. This training program successfully improved participants’ knowledge and practical skills, particularly in using digital tools for tourism promotion. Participants were able to produce creative marketing materials integrating the three dimensions of tourism marketing—image, halal, and sustainability—while applying rhetorical design principles using the digital applications of graphic design. However, several challenges were identified, including limited access to adequate equipment and licensed design software. To achieve greater and more sustainable economic impact, this study recommends extended technical mentoring, improved facility support, and ongoing evaluations that connect promotional activities to measurable indicators such as visitor engagement and income growth.